BlueTechValley Water Conference, May 1-2 - Uribes, Tom::::::::: (2013)
The 2013 BlueTechValley Water Conference: 'How Water Efficient Technologies Secure Future Food Supply' showcases innovation in the fields of water, energy and ag technology.